Impact of Public-Private Partnerships for transport infrastructure on Peruvian economic development - Del Carpio Castro, Luis (2023)
Objective: To determine the impact of Public-Private Partnerships (PPPs) of transportation infrastructure in the Peruvian economic development, during the period 2008-2021. Methodology: A quantitative, causal-type, non-experimental approach was employed, utilizing time series and panel data. Furthermore, a Cointegration and causality analyses were conducted. Before that, a development variable was created using Principal Component. Results: An increase of investments in transport infrastructure, made by PPPs, has a positive effect in economic development and the investments in port infrastructure have a greater impact compared to investments in airports, highways and railways, following that order. Conclusion: There exists a unidirectional short-term and long-term causality from the investment of transport infrastructure PPP towards economic development, except for road infrastructure, which it did not demonstrate short-term causality.